Answer :
-5x-10=2(x-4)
-5x-10=(2•x)(2•(-4)
-5x-10=2x-8
-5x-10+10=2x-8+10
-5x=2x+2
-5x-2x=2x-2x+2
-3x=2
-3x\-3=2\-3
x=0.666
x=0.67
-5x-10=(2•x)(2•(-4)
-5x-10=2x-8
-5x-10+10=2x-8+10
-5x=2x+2
-5x-2x=2x-2x+2
-3x=2
-3x\-3=2\-3
x=0.666
x=0.67
Let us take this step by step:
-5x - 10 = -2x - 8
Then you bring the variables in the same side (also reversing - to + or + to -):
-5x + 2x = 10 - 8
Do the addition and subtraction:
-3x = 2
x = \frac{2}{3}
-5x - 10 = -2x - 8
Then you bring the variables in the same side (also reversing - to + or + to -):
-5x + 2x = 10 - 8
Do the addition and subtraction:
-3x = 2
x = \frac{2}{3}